The effect of a web-based self-management training program on the quality of life of patients undergoing heart valve replacement: An experimental study - Zahra Hasani; Saeideh Mazloomzadeh; Shiva Khaleghparast; Saeid Hoseini; Hamed Taghiloo (Zanjan University of Medical Sciences and Health Services, 2024)
Background: The available literature shows the positive effect of self-management programs on the quality of life of patients with chronic diseases; however, this effect has not been investigated in patients undergoing heart valve replacement surgery. Objectives: The present study aimed to determine the effect of a web-based self-management training program on the quality of life of patients undergoing heart valve replacement. Methods: This research was an experimental study with a control group, which was conducted on 80 patients undergoing heart valve replacement surgery at Shahid Rajaei Cardiovascular Educational, Research and Therapeutic Institute in Tehran, Iran. Participants were divided into experimental and control groups by the block randomization method. The control group received the routine care. The experimental group received the web-based self-management training program in 5-7 people groups. The educational content of the sessions included medication management, emotional management, role management, decision-making and problem-solving skills, use of resources, communication with caregivers, and an activity program. The questionnaires included the demographic information form and the 12-Item Short Form Quality of Life Questionnaire (SF-12). Data were analyzed using the independent sample t-test, paired t-test, and analysis of covariance (ANCOVA) in SPSS 18 software. Results: The mean score of quality of life after the intervention showed a significant difference between the control and experimental groups (P=0.014). Comparison of the mean score of the quality of life of patients undergoing heart valve replacement in the experimental group before and after the intervention showed a statistically significant difference (P<0.001). Conclusion: According to the results of this study, it seems that self-management programs can improve the quality of life of patients undergoing heart valve replacement.